2013
DOI: 10.3945/ajcn.112.052183
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake

Abstract: Background: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants.Objective: The objective of the study was to identify common genetic variants that are associated with macronutrient intake.Design: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
176
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 51 publications
(54 reference statements)
19
176
1
3
Order By: Relevance
“…Whilst there is no direct evidence for the function of the rs838133 variant (or one in strong linkage disequilibrium), the A allele is very likely to represent a loss of FGF21 function, because it is very robustly associated with higher sugar and alcohol preference in people, a finding that is completely consistent with the genetic and pharmacological effects of FGF21 lowering in animal models, including non-human primates [1,2]. The apparently paradoxical association between the FGF21 A allele and higher circulating levels of FGF21 protein [12,14], may be caused by a feedback process that results in greater FGF21 production as a response to higher carbohydrate intake.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Whilst there is no direct evidence for the function of the rs838133 variant (or one in strong linkage disequilibrium), the A allele is very likely to represent a loss of FGF21 function, because it is very robustly associated with higher sugar and alcohol preference in people, a finding that is completely consistent with the genetic and pharmacological effects of FGF21 lowering in animal models, including non-human primates [1,2]. The apparently paradoxical association between the FGF21 A allele and higher circulating levels of FGF21 protein [12,14], may be caused by a feedback process that results in greater FGF21 production as a response to higher carbohydrate intake.…”
Section: Discussionsupporting
confidence: 65%
“…Whilst there is no direct evidence for the function of the rs838133 variant (or one in strong linkage disequilibrium), the A allele is very likely to represent a loss of FGF21 function, because it is very robustly associated with higher sugar and alcohol preference in people, a finding that is completely consistent with the genetic and pharmacological effects of FGF21 lowering in animal models, including non-human primates [1,2]. The apparently paradoxical association between the FGF21 A allele and higher circulating levels of FGF21 protein [12,14], may be caused by a feedback process that results in greater FGF21 production as a response to higher carbohydrate intake.The developers of therapies targeting FGF21 will be interested in the genotype-phenotype associations of the putative loss of function allele with a) higher percentage carbohydrate intake, b) higher alcohol intake, c) lower body fat percentage, d) altered body fat distribution, e) higher blood pressure, f) higher albumin to creatine ratio in the urine, g) higher LDL-cholesterol, h) higher triglycerides, but i) minimal if any effect on BMI and j) no evidence of an effect on type 2 diabetes or glycaemic traits. Of these associations, only that with higher percentage carbohydrate intake was convincingly shown before [13].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Increased fat intake in risk allele carriers was reported earlier [43,55,56]. Tanaka et al performed recently a meta-analysis of macronutrient intake in populations of European descent and showed that rs1421085 variant was associated with higher protein intake independently of BMI [59]. Corresponding results were demonstrated by the Malmo Diet and Cancer Study, where a higher percentage of energy from protein in diet was observed for A-allele carriers [60].…”
Section: Fto and Dietsupporting
confidence: 63%
“…[6][7][8] Preference for fatty foods is a complex trait regulated by genetic and environmental factors, but only a few such factors have been identified in human populations. [9][10][11][12][13][14] These include the opioid receptor mu-1 gene (OPRM1) 13 and prenatal exposure to maternal cigarette smoking (PEMCS).…”
Section: Introductionmentioning
confidence: 99%